MeCP2 post-translational modifications: a mechanism to control its involvement in synaptic plasticity and homeostasis? - Bellini, Elisa; Pavesi, Giulio; Barbiero, Isabella; Bergo, Anna; Chandola, Chetan; Nawaz, Mohammad S.; Rusconi, Laura; Stefanelli, Gilda; Strollo, Marta; Valente, Maria M.; Kilstrup-Nielsen, Charlotte; Landsberger, Nicoletta (Frontiers in Cellular Neuroscience, 2014)
Although Rett syndrome (RTT) represents one of the most frequent forms of severe intellectual disability in females worldwide, we still have an inadequate knowledge of the many roles played by MeCP2 (whose mutations are responsible for most cases of RTT) and their relevance for RTT pathobiology. Several studies support a role of MeCP2 in the regulation of synaptic plasticity and homeostasis. At the molecular level, MeCP2 is described as a repressor capable of inhibiting gene transcription through chromatin compaction. Indeed, it interacts with several chromatin remodeling factors, such as HDAC-containing complexes and ATRX. Other studies have inferred that MeCP2 functions also as an activator; a role in regulating mRNA splicing and in modulating protein synthesis has also been proposed. Further, MeCP2 avidly binds both 5-methyl- and 5-hydroxymethyl-cytosine. Recent evidence suggests that it is the highly disorganized structure of MeCP2, together with its post-translational modifications (PTMs) that generate and regulate this functional versatility. Indeed, several reports have demonstrated that differential phosphorylation of MeCP2 is a key mechanism by which the methyl binding protein modulates its affinity for its partners, gene expression and cellular adaptations to stimuli and neuronal plasticity. As logic consequence, generation of phospho-defective Mecp2 knock-in mice has permitted associating alterations in neuronal morphology, circuit formation, and mouse behavioral phenotypes with specific phosphorylation events. MeCP2 undergoes various other PTMs, including acetylation, ubiquitination and sumoylation, whose functional roles remain largely unexplored. These results, together with the genome-wide distribution of MeCP2 and its capability to substitute histone H1, recall the complex regulation of histones and suggest the relevance of quickly gaining a deeper comprehension of MeCP2 PTMs, the respective writers and readers and the consequent functional outcomes.